الحركة الأدبية في مواجهة المستجدات الحديثة في العصر العباسي - الحسن حسان (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
الشعر المحدث في العصر العباسي شغل الباحثين والدارسين قدامى ومحدثين لأنه حول الشعر العربي تحولاً جديداً لم يكن معروفاً من قبل، حيث واكب الشعراء في ذلك العصر طبيعة الحياة اليومية والثقافية والسياسية والاجتماعية فعبروا عنها وصوروها تصويراً فنياً إبداعياً، مما جعلهم يسيرون في ركب التطور والتجديد، فلم يحفلوا بمنهج القصيدة العربية القديمة من وقفة طللية وغيرها ونظموا بما يتفق مع حياتهم الجديدة، مما أثار حفيظة النقاد والأدباء فمنهم من ناصر الحداثة الجديدة في العصر، ومنهم من عارض تلك الحداثة متشبثاً بالقديم، ونشبت خصومة أدبية نقدية تجاه الشعر المحدث ومواكبته لطبيعة العصر، فكان من نتائج تلك الخصومة أنها أنتجت تياراً نقدياً فنياً جديداً وأن الشعر المحدث قد انتصر على القديم وأصبح له اتجاهات شعرية عديدة أبرزها الاتجاه الذاتي والواقعي والشعبي وذلك بفضل الشعراء المحدثين الذين حملوا راية التطور والتجديد فكان لهم الفضل أيضاً في تطور الشعر العربي عبر العصور وليكون منارة الأجيال القادمة إبداعاً وفناً. Scholars and researchers, old and modern, were much interested in the modern poetry at Al- Abbasid Period since it mad poetry undergo a new transformation that was unknown before: the poets, at that period, kept up with the nature of social political cultural every day life, expressing and portraying it artistically and creatively; this made them make their way to development and restoration, not caring about the Arabic poem approaches such as visiting the ruins and so on; therefore, they wrote poetry according to their new lives. This aroused the anger of critics and writers, some of whom advocated to old poetry. Hence, a critical literary disagreement on the modern poetry and its keeping up with the age nature arose. This disagreement, consequently, resulted in a new artistic critical current, indicating that the modern poetic trend, the most prominent of which are the personal trend and the public factual trend: all these were thanks to modern poets who carried the banner of restoration and development- the development of Arabic poetry to be, artistically and creatively, as a guiding light for the coming generations throughout ages.